Análise da mudança de um sistema de produção empurrado para puxado: uma pesquisa-ação em uma cadeia produtiva terceirizada de cosméticos - Fonseca, Henrique Varela (2020)
The objective of this thesis is to study the application of lean methodology in an outsourced cosmetics production chain, through the implementation of an intervention in the production system of the dyad formed between the cosmetics company and its outsourced manufacturer, changing the production process from a push to a pull system. The original context of this production chain under the push system presented a scenario with long lead times and unbalanced finished product and raw materials stocks, leading the author to propose an action research in which an intervention was developed in the production system of two SKUs to solve those issues. It was selected two SKUs from two different factories of the same outsourced manufacturer to evaluate the effects of this intervention in two different production environments. In this intervention, lean methodology tools were used as the value stream mapping that detailed the original state of the pushed system, allowing to collect and analyze the data from this original context. Then, the future state map was developed which considered the principle of lean methodology that guides the production system pulled by the real demand. The planning and execution of this intervention were detailed in this paper to present the preparation and training stages of the involved team, development of current and future maps, pull system calculation, implementation schedules and results evaluation. Following the implementation of this change, the sales forecast, lead time and inventory indicators were analyzed under the new pull production system condition. Sales forecast accuracy was improved by over 70%, lead time significantly reduced by about 65%, and an important reduction in inventory levels was identified with the two SKUs analyzed, with 18% for the SKU produced at the cream factory and about 37% for the fragrance SKU. In addition to these results, interviews with key participants of this intervention revealed the main challenges, benefits and opportunities in this process of promoting such a complex change in an outsourced production chain and in a highly volatile demand environment.